Community Assistance on Covid-19 Awareness in a Village - Mukhlisin, Mukhlisin; Umar, Muallief; Masrifatin, Yuni (STAI Miftahul ULa Nganjuk, 2023)
The Covid-19 pandemic has posed significant challenges, particularly in raising awareness about the importance of health protocols. This community service program aims to enhance the awareness of Covid-19 in Desa Sidoharjo by educating the community on preventive measures. The approach used in this project is Community Service, which involves the active participation of local residents in educational activities. The program includes distributing masks, training on proper handwashing, and conducting seminars on social distancing. The results show a significant improvement in the community's understanding of Covid-19 and the implementation of health protocols. Active participation in these activities indicates the program's success in raising awareness and encouraging behavioral changes in the community, ultimately contributing to the prevention of Covid-19 spread in the village.